Effect of Silver Nanowire Plasmons on Graphene Oxide Coatings Reduction for Highly Transparent Electrodes - Xingzhen Yan; Lu Zhou; Xuefeng Chu; Huan Wang; Fan Yang; Chao Wang; Yaodan Chi; Xiaotian Yang (Advances in Condensed Matter Physics)
We prepared transparent conducting composite electrodes composed of silver nanowires (Ag NWs) and reduced graphene oxide (r-GO). We present a simple approach to welding the cross-positions of the Ag NWs by applying pressure at a relatively low temperature (100°C). We examined the Ag NWs/r-GO composite films in terms of their transmission, conductivity, and stability. The plasmonic features of the Ag NWs were used to assist the ultraviolet (UV) light-induced reduction of the GO coating. The r-GO coatings used to form Ag NWs/r-GO composite structures increased the conductivity of the film by providing more efficient electron conductive pathways. The G/D intensity ratios of the GO and r-GO produced by the UV light-induced method without and with Ag NWs were 0.95, 1.01, and 1.04, respectively. The lowest sheet resistance of the composite films was 7 ohm/sq with approximately 82% transparency in the visible spectrum region. No degradation of the films was observed after 2 months. This excellent environmental stability might facilitate applications of Ag NWs/r-GO composite films in optoelectronic devices.